THE INFLUENCE OF DEMOGRAPHIC FACTORS (AGE, GENDER, EDUCATION AND INCOME) ON CONSUMER BUYING BEHAVIOR OF ONLINE SHOP - Rambi, Fiano Michael; Saerang, David Paul Elia; Rumokoy, Farlane Stevie (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
This study aims to analyze the influence of age, gender, education and income on consumer buying behavior of online shop. This study’s data is primary data obtained through the questionnaire distributed to online store consumers in Manado City. Multiple linear regression analysis Regression analysis was used and showed that the age education and income the same positive influence on consumer buying behavior, while gender has the opposite impact. Testing hypotheses partially shows that the value of the variable t for age and education greater than ttable and gender and income has the opposite comparison. Simultaneous hypothesis testing, where the value of the variable F value for these variable is greater than Ftable. which means that the four variables simultaneously affect the consumer buying behavior. The relationship model indicates that consumer buying behavior is influenced by age, gender, education and income while the rest percentage influenced by other excluded causes in this study. The result of analysis indicates that these variables to consumer buying behavior have a positive relationship. Keywords: consumer, buying behavior, demographic factors